A multi-level modeling approach examining PTSD symptom reduction during prolonged exposure therapy: moderating effects of number of trauma types experienced, having an HIV-related index trauma, and years since HIV diagnosis among HIV-positive adults. Issue 11 (2nd November 2017) - Junglen, Angela G.; Smith, Brian C.; Coleman, Jennifer A.; Pacella, Maria L.; Boarts, Jessica M.; Jones, Tracy; Feeny, Norah C.; Ciesla, Jeffrey A.; Delahanty, Douglas L.
ABSTRACT: People living with HIV (PLWH) have extensive interpersonal trauma histories and higher rates of posttraumatic stress disorder (PTSD) than the general population. Prolonged exposure (PE) therapy is efficacious in reducing PTSD across a variety of trauma samples; however, research has not examined factors that influence how PTSD symptoms change during PE for PLWH. Using multi-level modeling, we examined the potential moderating effect of number of previous trauma types experienced, whether the index trauma was HIV-related or not, and years since HIV diagnosis on PTSD symptom reduction during a 10-session PE protocol in a sample of 51 PLWH. In general, PTSD symptoms decreased linearly throughout the PE sessions. Experiencing more previous types of traumatic events was associated with a slower rate of PTSD symptom change. In addition, LOCF analyses found that participants with a non-HIV-related versus HIV-related index trauma had a slower rate of change for PTSD symptoms over the course of PE. However, analyses of raw data decreased this finding to marginal. Years since HIV diagnosis did not impact PTSD symptom change. These results provide a better understanding of how to tailor PE to individual clients and aid clinicians in approximating the rate of symptom alleviation. Specifically, these findings underscore the importance of accounting for trauma history and index trauma type when implementing a treatment plan for PTSD in PLWH.